Ownership and Usage of Mobile Devices Among Ophthalmology Residents and Attending Physicians: Identifying the Generation Gap - Al Owaifeer AM; Al Taisan A; Alqahtani B; Alburayk K; Alsubaie M; Alenezi SH (Advances in Medical Education and Practice, 2020)
Adi Mohammed Al Owaifeer,1,2 Abdulaziz Al Taisan,1 Bader Alqahtani,3 Khalid Alburayk,4 Majed Alsubaie,5 Saad H Alenezi6 1Faculty of Ophthalmology, College of Medicine, King Faisal University, Al-Ahsa, Saudi Arabia; 2King Khaled Eye Specialist Hospital, Riyadh, Saudi Arabia; 3Department of Ophthalmology, King Abdulaziz Medical City, Jeddah, Saudi Arabia; 4College of Medicine, Prince Sattam bin Abdulaziz University, Al-Kharj, Saudi Arabia; 5Dhahran Eye Specialist Hospital, Dhahran, Saudi Arabia; 6Department of Ophthalmology, College of Medicine, Majmaah University, Majmaah, Saudi ArabiaCorrespondence: Adi Mohammed Al OwaifeerFaculty of Ophthalmology, College of Medicine, King Faisal University, P.O. Box 400, Al-Ahsa 31982, Saudi ArabiaTel +966135808573Fax +966135800820Email aalowaifeer@kfu.edu.saBackground: Ophthalmology residents strongly rely on digital technology in training. This characteristic may not be shared by their teachers, attending physicians. Therefore, the aim of this study was to describe the ownership and usage of mobile devices among Saudi ophthalmology residents and their attending physicians and to compare ownership and usage patterns between both groups.Methods: A survey was conducted to determine the rates of ownership of mobile devices and the patterns of usage among Saudi ophthalmology residents and their attending physicians. The survey was sent to 305 eligible participants.Results: The overall response rate was 81%. The mean age of residents and attendings was 27.4 and 48.6 years, respectively. The ownership of mobile phones was higher among attendings (1.21 ± 0.4 vs 1.36 ± 0.5, p = 0.02), whereas the ownership of tablets was higher among residents (1 ± 0.6 vs 0.7 ± 0.6, p = 0.01). Residents utilized mobile devices to access online educational resources more frequently compared to attendings. A statistically significant difference between residents and attendings was reported in the utilization of wikis (91% vs 46%), e-books (90% vs 54%), file sharing sites (84% vs 52%), and vodcasts (78% vs 58%). Both groups also differed with regards to reasons of utilization. While residents most commonly used mobile devices to answer clinical questions on demand (87%) and to acquire basic knowledge (84%), the main reasons of utilization cited by attendings were to look up controversial issues (77%) and to connect with peers (72%).Conclusion: The two studied groups differ from each other in the type of devices owned, reasons for usage, and frequency of utilization. The difference in behavior between educators and their students can lead to a generation gap that halts the progress of residents’ training.Keywords: educational resources, medical education, health communication, digital technology